An Analysis of Textbook “English in Mind: Student’s Book Starter” for The 7th Year Students of Junior High School Based on Merdeka Curriculum - Encik Siti Adilah; H. Lalu Nurtaat; Kurniawan Apgrianto; Henny Soepriyanti (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study deals with analysis of textbook for the 7th year students of junior high school based on the latest curriculum, namely the Merdeka curriculum. The purpose of this study was to identify the material presented in the textbook as compatible for grade 7 junior high school. This study was a qualitative descriptive study. The method of this study was content analysis. The data source for this research is the English textbook "English in Mind: Student's Book Starter" published by Cambridge University Press written by Herbert Puchta and Jeff Strank in 2010. The textbook analysis in this study considered eight criteria, namely; (1) goals and approach divided into two, aims and objectives and the teaching and learning situations; (2) Design and organization are divided into two, the components of the textbook package and the organization of the textbook; (3) Language content is divided into two, grammar and vocabulary; (4) Skills are divided into 4 listening, reading, speaking and writing; (5) Topics are divided into two, topic and subject content, and social and cultural values; (6) Methodology; (7) Teacher's book; and (8) Practical concern. The results of the study show that the textbook fulfills all eight criteria. Based on the analysis, the textbook was classified as being of satisfactory quality and suitable for use in 7th grade junior high school.